Noninvasive intracranial pressure assessment by optic nerve sheath diameter: Automated measurements as an alternative to clinician-performed measurements - Netteland, Dag Ferner; Aarhus, Mads; Smistad, Erik; Sandset, Else Charlotte; Padayachy, Llewellyn; Helseth, Eirik; Brekken, Reidar (Frontiers in Neurology, 2023)
Introduction Optic nerve sheath diameter (ONSD) has shown promise as a noninvasive parameter for estimating intracranial pressure (ICP). In this study, we evaluated a novel automated method of measuring the ONSD in transorbital ultrasound imaging. Methods From adult traumatic brain injury (TBI) patients with invasive ICP monitoring, bedside manual ONSD measurements and ultrasound videos of the optic nerve sheath complex were simultaneously acquired. Automatic ONSD measurements were obtained by the processing of the ultrasound videos by a novel software based on a machine learning approach for segmentation of the optic nerve sheath. Agreement between manual and automated measurements, as well as their correlation to invasive ICP, was evaluated. Furthermore, the ability to distinguish dichotomized ICP for manual and automatic measurements of ONSD was compared, both for ICP dichotomized at ≥20 mmHg and at the 50th percentile (≥14 mmHg). Finally, we performed an exploratory subgroup analysis based on the software's judgment of optic nerve axis alignment to elucidate the reasons for variation in the agreement between automatic and manual measurements. Results A total of 43 ultrasound examinations were performed on 25 adult patients with TBI, resulting in 86 image sequences covering the right and left eyes. The median pairwise difference between automatically and manually measured ONSD was 0.06 mm (IQR −0.44 to 0.38 mm; p = 0.80). The manually measured ONSD showed a positive correlation with ICP, while automatically measured ONSD showed a trend toward, but not a statistically significant correlation with ICP. When examining the ability to distinguish dichotomized ICP, manual and automatic measurements performed with similar accuracy both for an ICP cutoff at 20 mmHg (manual: AUC 0.74, 95% CI 0.58–0.88; automatic: AUC 0.83, 95% CI 0.66–0.93) and for an ICP cutoff at 14 mmHg (manual: AUC 0.70, 95% CI 0.52–0.85; automatic: AUC 0.68, 95% CI 0.48–0.83). In the exploratory subgroup analysis, we found that the agreement between measurements was higher in the subgroup where the automatic software evaluated the optic nerve axis alignment as good as compared to intermediate/poor. Conclusion The novel automated method of measuring the ONSD on the ultrasound videos using segmentation of the optic nerve sheath showed a reasonable agreement with manual measurements and performed equally well in distinguishing high and low ICP.